Antigenicity of Anisakis simplex s.s. L3 in parasitized fish after heating conditions used in the canning processing1. (26th June 2014) - Tejada, Margarita; Olivares, Fabiola; de las Heras, Cristina; Careche, Mercedes; Solas, María Teresa; García, María Luisa; Fernandez, Agustín; Mendizábal, Angel; Navas, Alfonso; Rodríguez‐Mahillo, Ana Isabel; González‐Muñoz, Miguel
Abstract BACKGROUND Some technological and food processing treatments applied to parasitized fish kill the Anisakis larvae and prevent infection and sensitization of consumers. However, residual allergenic activity of parasite allergens has been shown. The aim here was to study the effect of different heat treatments used in the fish canning processing industry on the antigen recognition of Anisakis L3. Bigeye tuna (Thunnus obesus) and yellowfin tuna (Thunnus albacares) were experimentally infected with live L3 Anisakis. After 48 h at 5 ± 1 °C, brine was added to the muscle, which was then canned raw (live larvae) or heated (90 °C, 30 min) (dead larvae) and treated at 113 °C for 60 min or at 115 °C for 90 min. Anisakis antigens and Ani s 4 were detected with anti‐crude extract and anti‐Ani s 4 antisera respectively. RESULTS Ani s 4 decreased in all lots, but the muscle retained part of the allergenicity irrespective of the canning method, as observed by immunohistochemistry. Dot blot analysis showed a high loss of Ani s 4 recognition after canning, but residual antigenicity was present. CONCLUSION The results indicate that heat treatment for sterilization under the conditions studied produces a decrease in Ani s 4 and suggest a potential exposure risk for Anisakis‐sensitized patients. © 2014 Society of Chemical Industry